2015
DOI: 10.1099/vir.0.000102
|View full text |Cite
|
Sign up to set email alerts
|

Defects in RNA polyadenylation impair both lysogenization by and lytic development of Shiga toxin-converting bacteriophages

Abstract: In Escherichia coli, the major poly(A) polymerase (PAP I) is encoded by the pcnB gene. In this report, a significant impairment of lysogenization by Shiga toxin-converting (Stx) bacteriophages (W24 B , 933W, P22, P27 and P32) is demonstrated in host cells with a mutant pcnB gene. Moreover, lytic development of these phages after both infection and prophage induction was significantly less efficient in the pcnB mutant than in the WT host. The increase in DNA accumulation of the Stx phages was lower under condit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 54 publications
2
18
0
Order By: Relevance
“…PAP I can bind to the 3= terminus of mRNA and further polyadenylates the mRNA, generating substrates readily degraded by PNPase (40). Dysfunction of PAP I has also been reported to inhibit the induction of the Stx-converting phage (19). Consistent with the inhibition of Stx2 prophage induction and reduction of Stx2 phage abundance, cinnamon oil at 0.75ϫ or 1ϫ MIC eliminated both PAP I and PNPase content.…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…PAP I can bind to the 3= terminus of mRNA and further polyadenylates the mRNA, generating substrates readily degraded by PNPase (40). Dysfunction of PAP I has also been reported to inhibit the induction of the Stx-converting phage (19). Consistent with the inhibition of Stx2 prophage induction and reduction of Stx2 phage abundance, cinnamon oil at 0.75ϫ or 1ϫ MIC eliminated both PAP I and PNPase content.…”
Section: Discussionmentioning
confidence: 52%
“…5A), indicating that additional factors are involved with the inhibitory effect of Stx2 prophage induction. Previous studies showed that dysfunction of PNPase or PAP I, important enzymes in RNA polyadenylation, impaired the lytic development of the Stx2 phage (18,19). Therefore, we evaluated the production of PNPase and PAP I proteins as well as the expression of hfq mRNA, which is an important factor involved in the function of both enzymes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To test effects of various commonly used drinks on efficiency of Stx prophage induction in E. coli, MG1655 strain (Jensen 1993) and its derivative carrying a modified (for safety reasons) Stx 933W prophage, 933W Dstx2::cat-gfp (Nowicki et al 2015), were employed. Following drinks were tested at indicated final concentrations in culture medium: Coca-Cola (final concentration 5%), Nestea (final concentration 5%), and vodka _ Zubrówka (final ethanol concentration 1%).…”
Section: Resultsmentioning
confidence: 99%
“…Levels of mRNAs were measured by RT-qPCR 15 min after λ phage infection and 35 min after infection with Stx phages (Φ24 B , 933W, P32, P27, P22). These post-infection times were chosen according to our prior knowledge of development of these phages in E. coli bacteria [26,32]. As shown in Fig.…”
Section: The Ea22 Gene Expression During Phage Infectionmentioning
confidence: 99%